Robust B Cell Responses Predict Rapid Resolution of Lyme Disease - Blum, Lisa K.; Adamska, Julia Z.; Martin, Dale S.; Rebman, Alison W.; Elliott, Serra E.; Cao, Richard R. L.; Embers, Monica E.; Aucott, John N.; Soloski, Mark J.; Robinson, William H. (Frontiers in Immunology, 2018)
Lyme disease (Borrelia burgdorferi infection) is increasingly recognized as a significant source of morbidity world-wide. Here, we show that blood plasmablasts and CD27- memory B cells are elevated in untreated Lyme disease, with higher plasmablast levels associated with more rapid resolution of clinical symptoms. Stronger serum reactivity to surface proteins and peptides from B. burgdorferi was also associated with faster resolution of clinical symptoms. Through molecular identifier-enabled antibody heavy chain sequencing of bulk B cells and single-cell paired-chain antibody sequencing of blood plasmablasts, we characterized immunoglobulin gene usage patterns specific to B. burgdorferi infection. Recombinantly expressed antibodies from expanded lineages bound B. burgdorferi antigens, confirming that these clones are driven by the infection. Further, recombinant sequence-derived antibodies were functional, inhibiting growth of B. burgdorferi in vitro. Elevations and clonal expansion of blood plasmablasts were associated with rapid return to health, while poor plasmablast responses were associated with a longer duration of symptoms following treatment. Plasmablasts induced by B. burgdorferi infection showed preferential antibody gene segment usage, while bulk sequencing of total B cells revealed convergent CDR3 motifs specific to B. burgdorferi-infected patients. Our results show that robust plasmablast responses encoding Bb-static antibodies are associated with more rapid resolution of Lyme disease, and these antibodies could provide the basis for next-generation therapeutics for Lyme disease.